Improving care for patients with Clostridioides difficile infection: A clinical practice and healthcare systems perspective - Hocking, Lucy; Wilcox, Mark; Petrosillo, Nicola; Griffin, Paul; Steiner, Theodore; Attara, Gail; Doré, Joel; Cabling, Mark; Stockwell, Stephanie; Romanelli, Robert J.; Marjanovic, Sonja (Frontiers in Medicine, 2023)
Arriving at a C. difficile infection (CDI) diagnosis, treating patients and dealing with recurrences is not straightforward, but a comprehensive and well-rounded understanding of what is needed to improve patient care is lacking. This paper addresses the paucity of multidisciplinary perspectives that consider clinical practice-related and healthcare system-related challenges to optimizing care delivery. We draw on narrative review, consultations with clinical experts and patient representatives, and a survey of 95 clinical and microbiology experts from the UK, France, Italy, Australia and Canada, adding novel multi-method evidence to the knowledge base. We examine the patient pathway and variations in clinical practice and identify, synthesize insights on and discuss associated challenges. Examples of key challenges include the need to conduct multiple tests for a conclusive diagnosis, treatment side-effects, the cost of some antibiotics and barriers to access of fecal microbiota transplantation, difficulties in distinguishing recurrence from new infection, workforce capacity constraints to effective monitoring of patients on treatment and of recurrence, and ascertaining whether a patient has been cured. We also identify key opportunities and priorities for improving patient care that target both clinical practice and the wider healthcare system. While there is some variety across surveyed countries’ healthcare systems, there is also strong agreement on some priorities. Key improvement actions seen as priorities by at least half of survey respondents in at least three of the five surveyed countries include: developing innovative products for both preventing (Canada, Australia, UK, Italy and France) and treating (Canada, Australia, Italy) recurrences; facilitating more multidisciplinary patient care (UK, Australia and France); updating diagnosis and treatment guidelines (Australia, Canada and UK); and educating and supporting professionals in primary care (Italy, UK, Canada, Australia) and those in secondary care who are not CDI experts (Italy, Australia and France) on identifying symptoms and managing patients. Finally, we discuss key evidence gaps for a future research agenda.